The Quality Assessment of Teaching Delivery Based on The National Occupational Skills Standard at MARA High Skills College - Bidin, Bizaisham; Azman, Mohamed Nor Azhari; Kiong, Tee Tze; Khairudin, M. (International Journal of Psychosocial Rehabilitation, 2020)
Skill Training in Malaysia is an important platform to produce skilled manpower for the local technology industry. Consequently, the delivery of teaching by the academic staff is an important factor to ensure the transfer of knowledge and skills are delivered to the students. Skill training in Malaysia is applied based on the Competency-Based Training (CBT) approach which is a standardized teaching approach at the national level that emphasizes the method of four-step patterns that comprises preparation, delivery, application, and validation in the teaching process. This method is used to ensure the quality of teaching can be delivered effectively. This research was conducted at the MARA High Skills College (KKTM) among the instructors who have completed the teaching training at the Centre for Instructor and Advanced Skill Training (CIAST). The teaching training at KKTM was evaluated based on the standard guideline. The quality of teaching delivery was evaluated using the National Occupational Skills Standard (NOSS).